Incorporation of titania nanoparticles in elastomer matrix to develop highly reinforced multifunctional solution styrene butadiene rubber composites. (24th January 2019) - Das, Chayan; Bansod, Naresh D.; Kapgate, Bharat P.; Rajkumar, K.; Das, Amit
Abstract: Titania nanoparticles are introduced in situ into SSBR matrix (solution of styrene butadiene rubber) by solution sol-gel method under controlled reaction condition that shows outstanding reinforcing efficiency because of its favourable morphological features and enhanced polymer-filler interaction. Surface treatment of titania particles in reactive sol-gel system using an organosilane, TESPT (bis-(3-triethoxysilylpropyl)-tetrasulfide) further strengthens the reinforcement effect. Notably, more than 85% conversion of titania from it's precursor (titanium n-butoxide, TNB) is achieved within 1 h reaction time without employing any catalyst. Additionally, controlled growth of titania particles inside rubber matrix imparts particular characteristics of the titania particles that enables them to deliver rich dielectric and antifungal properties to the composites. In-depth investigation of the composites including rheological, thermal, morphological, mechanical, dynamic mechanical, dielectric and antifungal studies have been carried out and structure-property relationship is established in respect to SSBR gum and externally titania filled composites prepared at similar condition. Graphical abstract: Image 1 Highlights: Titania is incorporated in situ inside SSBR matrix under optimized sol-gel reaction condition. Appreciable conversion of titania from its precursor is achieved even without using any catalyst. In situ titania shows superior reinforcing efficiency in enhancing the tensile properties of the composites. In situ titania filled SSBR samples demonstrate moderate dielectric and antimicrobial properties. Salinization of titania by TESPT improves filler dispersion and enhances rubber-filler interaction.